Description and psychometric properties of a prototype to test tactile acuity in the neck. (February 2021) - Olthof, Nick A.; Harvie, Daniel S.; Henderson, Courtney; Thompson, Brendan; Sharp, Robert; Craig-Ward, Lauren; Weermeijer, Jeroen D.; Sterling, Michele; Moseley, G. Lorimer; Coppieters, Michel W.
Abstract: Background: Clinical tools assessing tactile acuity in people with persistent pain have limitations. Therefore, a novel and semi-automated tool was developed: The Imprint Tactile Acuity Device (iTAD). Aim: To describe the iTAD prototype and present the psychometric properties of its tactile acuity assessments: the localisation test, the orientation test and the overall score (mean of both tests). Method: A test-retest design with fifty healthy participants was used to assess intra-rater reliability (ICC(2.1) ), internal consistency (ICC(2.4) ) and measurement error (SEM) of the three assessments (0–100% accuracy scores each) performed at the neck. Using a known-group comparison design, balanced by age and sex, scores of thirty individuals with persistent neck pain were compared to thirty healthy controls to determine construct validity. Results: The ICC(2, 1) and ICC(2, 4) were 0.60 and 0.78 for the localisation test, 0.66 and 0.77 for the orientation test, and 0.73 and 0.84 for the overall score. The SEMs were 9.0%, 8.1% and 6.0%, respectively. No fixed or proportional bias, or signs of heteroscedasticity were observed. Overall, no between group differences were observed ( p  = 0.49). In the male subgroup, however, the overall score was lower for people with neck pain than for healthy participants (mean difference (SE); 7.6% (2.5); p  = 0.008). Discussion: The tactile acuity assessments of the iTAD demonstrate moderate reliability and good internal consistency. Measurement errors appear comparable to currently preferred methods. Clear construct validity was not established, but results may be biased by design issues of the prototype. Taken together, the iTAD shows promise but further fine-tuning is needed. Highlights: A semi-automated device was developed to test tactile acuity in chronic neck pain. A technical description of a prototype device and its two tests are presented. Reliability estimates were moderate to good, comparable to traditional measures. Construct validity was not clearly established, possibly due to design issues. The novel tactile testing device shows promise, but fine-tuning is needed.